The Importance of Promotion Costs and Training Costs for Islamic Rural Bank in Indonesia by BPRudent - Nur Wahyu Ningsih; Ridwansyah Ridwansyah Ridwansyah; Sinta Ayu Purnamasari (ITB AAS INDONESIA Surakarta, 2020)
This research tested the influence of Islamic Rural Bank promotion cost and training cost towards Islamic Rural Bank profitability in Indonesia. Research variable used promotion cost and training cost which were allocated by Islamic Rural Bank, while profitability used proxy Return on Asset (ROA). This research is explanatory research by using quantitative approach. Sampling technique conducted was quota sampling and it found 4 Islalmic Rural Bank in Indonesia period 2013-2017. Finding indicated that there was no influence promotion cost and training cost towards profitability of Islamic Rural Bank in Indonesia. Regression analysis conducted showed that Islamic Rural Bank could optimize education cost and training cost based on each division of Islamic Rural Bank and maximize promotion cost to introduce product and service in appropriate segment of long term so that each Islamic Rural Bank in Indonesia can present their company's performance to the maximum on the BPRudent Platform